If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.08(y-2) + 0.18=0.16y-0.6
We simplify the equation to the form, which is simple to understand
0.08(y-2) + 0.18=0.16y-0.6
Reorder the terms in parentheses
+( + 0.08y-0.16) + 0.18=0.16y-0.6
Remove unnecessary parentheses
+ 0.08y-0.16 + 0.18=0.16y-0.6
We move all terms containing y to the left and all other terms to the right.
+ 0.08y-0.16y=-0.6 + 0.16-0.18
We simplify left and right side of the equation.
-0.08y=-0.62
We divide both sides of the equation by -0.08 to get y.
y=7.75
| 6x+15=3+8x-8 | | 2+6xt=-9 | | 3x^2-5x+2=4x+2 | | b=a^3-(a-3) | | 4(x+1)/8=3x-2 | | p=2x^2+18x+332 | | 2A+4=16 | | 7x+25x^2+4=5+7x | | 2x+7(3x-13)=47 | | 9(X-1)+X=8(3-X)-6 | | 0.04+X=74.52 | | y+2=-6/5+6/5 | | 13+2r=3r+7 | | 3(5-x)=9(15x-5) | | x/8=54 | | 3.75+3y=6 | | f(x)=8-7(4x+2) | | 2x+9=1x+1 | | 6x+3(2x+2)=102 | | 31=x+2x+(3x+1) | | 2x^2-5x-12.5=0 | | 2x^2-5x-12.51=0 | | 5x+7y/3(x+y) | | -3x-4=-6-5x | | 3x+5(25-x)=89 | | 7x+12y=34 | | 2(x+2)=3(x+6) | | 7x+12y=86 | | 3x+5(25-5)=89 | | 4(X+1)-2=6(5-X)+3 | | -3-2(x+4)=25 | | ln(2x+6)=-10 |